(untitled) (Pedagogy of Higher and Secondary Education, 1999)
What is creativity? The integration of creative work and pedagogical process. The author of the present article tries to find answers to these questions and in this connection pays special attention to the principle of humanization in the system of pedagogical principles of organizing pupils’ studies and creative activities.